Adult-Specific Life Outcomes of Cleft Lip and Palate in a Western Australian Cohort. (November 2018) - Nicholls, Wendy; Harper, Craig; Robinson, Suzanne; Persson, Martin; Selvey, Linda
Background: People with a cleft of the lip and/or palate (CL/P) differ from their peers due to their facial appearance, hearing and speech difficulties, and the significant time spent attending appointments and recovering from surgical interventions. These differences may impact life outcomes including occupation, income, education, relationships, psychosocial health issues, and lifestyle choices. Methodology: A self-administered questionnaire was posted to 338 former and current patients of the Cleft Lip and Palate Unit of Princess Margaret Hospital (PMH), Perth, Western Australia. Results: Completed questionnaires were returned by 158 former and current patients. In comparison to the Australian Bureau of Statistics, study participants attained equivalent highest education levels, full-time annual income levels, occupational categories, employment rates, and home ownership levels. They did not marry later and demonstrated positive health–related lifestyle behaviors. However independent living was significantly delayed, and the number of romantic relationships, marriages, and children was lower, with separation/divorce rates also being lower. A key finding was that 78% of participants self-reported that they experienced at least 1 psychosocial health issue and more than half experienced anxiety and/or depression. Conclusion: When comparing the sociological outcomes for the study participants, the psychosocial outcomes were the areas of most concern. Further investigation is required to determine the causes for the high self-reported rates of anxiety and/or depression found in this study.